A comparative study of the needle folded mesophyll in Pinus and Cedrus (Pinaceae) species - G.K. Zvereva (Известия высших учебных заведений. Поволжский регион: Естественные науки, 2022)
Background. The structure of the assimilatory tissue of the leaves at conifers studied mainly on cross-sections. The purpose of the study is to compare the features of the 3D forms of assimilative cells and the structure of the needle mesophyll in the species of the Pinus and Cedrus genera. Materials and methods. The structure of photosynthetic parenchyma was studied in two-year-old needles on shortened shoots by the example of 10 species of the genus Pinus (5 species of the subgenus Pinus, 5 species of the subgenus Strobus) and 3 species of the genus Cedrus. Leaf samples were fixed in mixture of Hammalunda. The spatial forms of assimilative cells and their mutual arrangement were investigated using a light microscope in the middle part of needles on transverse, paradermal and radial sections. Results and conclusions. The mesophyll of needles in species of the genera Pinus and Cedrus is mainly represented by folded cells, which for the most part differ in size and features of their spatial configuration. The longest assimilative cells of needles are characteristic of species of the genus Cedrus, and the shortest and thickest ones are characteristic of the subgenus Strobus. In the subgenus Pinus, the folded cells are generally flat; they have complex lobed shapes on the cross sections and elongated oval projections on the radial sections. In species of the subgenus Strobus, a significant part of the folded cells is thicker and more complex configurations, in which the lobed projections on cross sections are combined with different variants of cellular and semi-cellular forms in the longitudinal direction. Chlorenchyma of needles in species in the genus Cedrus consists mainly of flat folded cells with a small participation of folded-sinuate and folded-semi-cellular, as well as cells of a simple form. In the species of the genus Cedrus, in addition to well-pronounced lobes, projections of assimilation cells are often distinguished by small rounded teeth, which appear on both the transverse and radial sections of the needles. In the needles chlorenchyma at all species, cells of the subhypodermal layer are distinguished, having palisade- like protrusions, the height of which is more than width at species of the subgenus Pinus by 1.2–1.8 times, the subgenus Strobus by 1.1–1.4 times, and in representatives of the genus Cedrus – 1.7–2.6 times. They are almost perpendicular to the leaf surface and create an analogy of palisade tissue.